META-ANALISIS PENGARUH PENGGUNAAN MIND MAPPING TERHADAP HASIL BELAJAR IPS SD - Bambang Tri Kuntoro; Nyoto Hardjono (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
The purpose of this research was to re-analyze the effect of before and after the use of mind mapping in improving the learning outcomes of elementary school social studies (IPS). The study used a meta-analysis method. This research begins by formulating research topics, then developed again into the formulation of research problems, and at the final stage is to search relevant articles for data collection. Data was obtained by searching online journals through google Scholar with search keywords "mind mapping", "social studies learning outcomes", and "elementary social studies learning". As many as 20 articles were found, but only 11 articles were relevant to this study. The data obtained is processed again using quantative methods. Based on the results of the analysis of mind mapping proven to be able to improve student learning outcomes with the lowest to highest average of 12.95 - 93.05% with the average final result 40.17%.